Rancang Bangun Sistem Monitoring Suhu dan Kelembapan serta Kendali Dua Heater pada Kubikel 20 kV Berbasis Sistem Informasi Geografis - Rahmadani, Arief; Windarko, Novie Ayub; Raharja, Lucky Pradigta Setiya (Majalah Ilmiah Teknologi Elektro, 2022)
One of the disturbances that occur in the medium-voltage switchgear or cubicle 20 kV one of the disturbances that occur in cubicle 20 kV is when the temperature and humidity conditions are high, then one-day water vapor will arise that sticks to the cubicle wall and affects the corona. Therefore, the cubicle has a heater to heat the space to maintain the humidity. However, when in the field, the heater performance condition is often less than optimal and does not work. Under these conditions, a temperature and humidity monitoring system and a control system for two heaters are needed to prevent damage to the heater. The system is built using the STM32F103C8T6 microcontroller, the DHT-22 sensor is equipped with an exhaust fan to maintain the cubicle termination room temperature. The minimum permissible temperature parameter is 35 C to a maximum limit of 40 C with humidity below 90% following the cubicle brand datasheet, Schneider, and IEC 62271-1 standard. Furthermore, the data from the monitoring can be displayed on the LCD and a website-based Geographic Information System. With this tool, it can facilitate the community, especially the PLN, in the process of monitoring and maintaining cubicles 20 kV.